PENGARUH LAMA PENYIMPANAN TERHADAP PERKECAMBAHAN BIJI Stachytarpheta jamaicensis (L.) Vahl. [Effect of Seed Storage Duration on Seed Germination of Stachytarpheta jamaicensis (L.) Vahl.] - Solikin, Solikin (Research Center for Biology-Indonesian Institute of Sciences, 2014)
Stachytarpheta jamaicensis (L.) Vahl. belongs to family Verbenaceae which has potential as medicinal and ornamental plant. Research on determination of the effect of storage duration on seed germination of Stachytarpheta jamaicensis (L.) Vahl. was conducted in the glass house of Purwodadi Botanic Garden from July 2012 - July 2013. Experiment used a completely randomized design with treatments storage duration namely: S0 = no stored ; S1 = stored for 2 months ; S2 = stored for 5 months ; S3 = stored for 8 months and S4 = stored for 12 months. The treatments was replicated 5 times with 100 seeds for each replication. The seeds were sowed on river sand medium sifted with 2 mm sieve mess at about 0.5 cm deep, in polybags ( 15x10 cm ). The polybags were placed in a plastic box 38 x 28 x 13 cm and covered by transparent plastic and black paranet. Variables measured were germination percentage and daily germination rate. The results showed that the seed storage duration had significantly affected seed germination rate of Stachytarpheta jamaicensis (L.) Vahl.. The highest seed germination (96.8 %) was recorded for the treatment of eight months storage duration (S3). Whereas the fastest germination rate (5.53 days) was observed on the treatment of two months storage period.